Pancreatic resection with perioperative drug repurposing of propranolol and etodolac: trial protocol of the phase-II randomised placebo controlled PROSPER trial - Hüttner, Felix; Rooman, Ilse; Bouche, Gauthier; Knebel, Phillip; Hüsing, Johannes; Mihaljevic, André Leopold; Hackert, Thilo; Strobel, Oliver; Büchler, Markus W.; Diener, Markus K. (BMJ open, 2020)
Introduction Pancreatic cancer is the fourth-leading cause of cancer-related death in developed countries. Despite advances in systemic chemotherapy, the mainstay of curative therapy for non-metastatic disease is surgical resection. However, the perioperative period is characterised by stress and inflammatory reactions that can contribute to metastatic spread and disease recurrence. Catecholamines and prostaglandins play a crucial role in these reactions. Therefore, a drug repurposing of betablockers and cyclooxygenase inhibitors seems reasonable to attenuate tumour-associated inflammation by inhibiting psychological, surgical and inflammatory stress responses. This may cause a relevant antitumourigenic and antimetastatic effect during the perioperative period, a window for cancer-directed therapy that is currently largely unexploited. - Methods and analysis This is a prospective, single-centre, two-arm randomised, patient and observer blinded, placebo-controlled, phase-II trial evaluating safety and feasibility of combined perioperative treatment with propranolol and etodolac in adult patients with non-metastatic cancer of the pancreatic head undergoing elective pancreatoduodenectomy. 100 patients fulfilling the eligibility criteria will be randomised to perioperative treatment for 25 days perioperatively with a combination of propranolol and etodolac or placebo. Primary outcome of interest will be safety in terms of serious adverse events and reactions within 3 months. Furthermore, adherence to trial medication will be assessed as feasibility outcomes. Preliminary efficacy data will be evaluated for the purpose of power calculation for a potential subsequent phase-III trial. The clinical trial is accompanied by a translational study investigating the mechanisms of action of the combined therapy on a molecular basis. - Ethics and dissemination The PROSPER-trial has been approved by the German Federal Institute for Drugs and Medical Devices (reference number 4042875) and the Ethics Committee of the Medical Faculty of the University of Heidelberg (reference number AFmo-385/2018). The final trial results will be published in a peer-reviewed journal and will be presented at appropriate national and international conferences. - Trial registration numbers DRKS00014054; EudraCT number: 2018-000415-25.